17 β-Estradiol promotes vascular endothelial growth factor expression via the Wnt/β-catenin pathway during the pathogenesis of endometriosis. (12th July 2016) - Zhang, Ling; Xiong, Wenqian; Xiong, Yao; Liu, Hengwei; Liu, Yi
Abstract : STUDY HYPOTHESIS: Do estrogen and Wnt/β-catenin signaling promote vascular endothelial growth factor (VEGF) expression in endometriosis and how? STUDY FINDING: 17β-Estradiol (E2 )-drives β-catenin triggered up-regulation of VEGF in effector human primary endometrial stromal cells (ESCs) and thus enhances their ability to establish a new blood supply to the human exfoliated endometrium. WHAT IS KNOWN ALREADY: Implantation and survival of exfoliated endometrium is crucially dependent on neovascularization and Wnt/β-catenin signaling plays an important role in stimulating angiogenesis. STUDY DESIGN, SAMPLES/MATERIALS, METHODS: Expression levels of VEGF mRNA, estrogen receptor α (ERα) and β-catenin protein were measured in ovarian endometriosis, eutopic endometrium of endometriosis patients and normal endometrium with real-time RT–PCR and western blot. ESCs were treated with 10 nM E2 for different times in order to evaluate the effect of E2 on ERα, β-catenin and VEGF expression in these cells. Human endometrial stromal cells (T HESCs) were cultured for transfection with expression vectors and siRNA constructs and used in chromatin immunoprecipitation (ChIP) and luciferase assays, which were conducted to clarify the regulation mechanism of E2 on VEGF. MAIN RESULTS AND THE ROLE OF CHANCE: VEGF, ERα and β-catenin expression was increased in endometriotic lesions compared with normal endometrium. E2 could promote ERα, β-catenin and VEGF expression in ESCs. ChIP and luciferase assays revealed that E2 up-regulated β-catenin expression by binding to the estrogen response element site on the β-catenin promoter. β-Catenin stabilization could activate Wnt/β-catenin signaling, which has a direct transcriptional effect on VEGF gene expression. LIMITATIONS, REASONS FOR CAUTION: Endometriotic lesions were all from ovarian endometriosis and may differ from other type of endometriosis. WIDER IMPLICATIONS OF THE FINDINGS: These promising results improve the body of knowledge on endometriosis pathogenesis and could open up new therapeutic strategies for the treatment of endometriosis. STUDY FUNDING AND COMPETING INTEREST(S): This project was supported by the National Natural Science Foundation of China (grant no. 81170545 Y.L. and 81471439 Y.L.). None of the authors has any conflicting interests to declare.